Thermocuring conductive polyurethane structural adhesive and preparation method thereof

By introducing polyester/polyether diols, catalysts and organic conductive materials into conductive polyurethane glue, and using polyisocyanate as curing agent, the shortcomings of conductive polyurethane glue in toughness, conductivity and curing efficiency are solved, and the inability to conduct conductive polyurethane glue is achieved. High performance bonding effect in high temperature environments.

CN119490812APending Publication Date: 2025-02-21ZHEJIANG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411506983.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing conductive polyurethane glue has shortcomings in toughness, conductivity and curing efficiency, especially under high temperature and high stress conditions, which affects the wide range of practical applications.

Method used

By introducing polyester/polyether diols, catalysts and organic conductive materials, especially polyaniline, polypyrrole, etc. into the adhesive, combined with polyisocyanate as a curing agent, the reaction conditions are regulated to achieve rapid curing.

Benefits of technology

It significantly improves the conductivity and toughness of the colloid, ensures that the material has excellent mechanical strength and high elongation of break under high temperature environments, and solves the shortcomings of existing conductive polyurethane glues in terms of curing efficiency, toughness and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490812A_ABST
    Figure CN119490812A_ABST
Patent Text Reader

Abstract

The invention provides a thermocuring conductive polyurethane structural adhesive and a preparation method thereof, and aims to overcome the defects of the existing conductive polyurethane adhesive in the aspects of toughness, conductivity and curing efficiency. The preparation method comprises the following steps: firstly, taking polyester / polyether glycol, a catalyst and an organic conductive material as a glue A of the two-component glue (adjusting the proportion of each component to realize corresponding performance), taking a polyisocyanate curing agent as a glue B, uniformly smearing the glue A and the glue B which are mixed according to a certain proportion on a surface to be bonded during use, and the component coated with the AB glue is accurately aligned with the component to be bonded, and finally, the bonded component containing the AB glue is heated and cured, so that the polyurethane structural adhesive with excellent mechanical strength and conductivity is formed. After being cured, the adhesive not only shows good flexibility and high elongation at break, but also has stable conductivity, is suitable for bonding and packaging electronic elements in a high-temperature environment, is particularly suitable for the fields of automobiles, aviation and electronic products, and has remarkable application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a thermally cured conductive polyurethane structural adhesive and a preparation method thereof. Background Art

[0002] In the current field of materials science, conductive polyurethane structural adhesives are widely used in the bonding and packaging of electronic components due to their versatility. However, existing conductive polyurethane adhesives often show deficiencies in toughness, conductivity, and curing efficiency, especially under high temperature and high stress conditions, their performance is not stable enough, which affects the wide range of their practical applications. Therefore, it is particularly important to develop a new type of thermal curing conductive polyurethane structural adhesive that can overcome these challenges. Summary of the invention

[0003] In view of the above problems, the present invention provides a heat-curing conductive polyurethane structural adhesive and a preparation method thereof to meet the urgent demand for high-performance conductive adhesives in the market. By introducing polyester / polyether diols, catalysts and organic conductive materials, especially polyaniline, polypyrrole, etc., into the adhesive, the conductivity and toughness of the colloid can be effectively improved. This method uses polyisocyanate as a curing agent and achieves rapid curing by reasonably regulating the reaction conditions, thereby overcoming the shortcomings of existing conductive polyurethane adhesives in curing efficiency, toughness and conductivity, and provides an innovative and efficient solution for the high-temperature environment application of electronic components.

[0004] The specific technical scheme of the present invention is as follows: A method for preparing a heat-curing conductive polyurethane structural adhesive, comprising the following steps: First, a polyester / polyether diol, a catalyst and an organic conductive material are prepared into a two-component glue A glue, and the proportion of each component is adjusted to achieve the desired performance; at the same time, a polyisocyanate curing agent is used as B glue. The above-mentioned A glue and B glue constitute a polyurethane structural adhesive with conductive properties. When in use, the mixed curing process of the A glue and the B glue is: according to a certain ratio, the mixed A glue and the B glue are evenly applied to the surface to be bonded to ensure uniform coverage, and then the parts coated with the A glue and the B glue are accurately aligned with the parts to be bonded, and finally thermally cured at 80-170 degrees Celsius, and the reaction time is 0.5-3 hours.

[0005] Furthermore, the polyester / polyether diol includes one or more of polyethylene glycol (PEG), polypropylene glycol (PPG), polybutylene glycol (PBD), polytetramethylene glycol (PTMG), polycaprolactone (PCL) and polycarbonate diol (PCDL), and its molecular weight ranges from 200 to 1000. The polyisocyanate used is one or more of HDI trimer curing agent, triphenylmethane triisocyanate or dimethyltriphenylmethane tetraisocyanate. In addition, the catalyst can be a tin-based catalyst (such as dibutyltin diglycolate, dibutyltin diallyl oxide) and a lead-based catalyst. In order to enhance conductivity, the organic conductive material can be selected from one or more of polyaniline (PANI), polypyrrole (PPy) or polyethylenethiophene (PEDOT). Finally, the molar ratio of the polyester / polyether diol in the A glue to the isocyanate group in the polyisocyanate is 0.95:1 to 1:1.05, The present invention also provides a heat-curing conductive polyurethane structural adhesive, which is prepared by the preparation method as described above and includes A glue and B glue, wherein the A glue is composed of polyester / polyether diol, a catalyst and an organic conductive material; and the B glue is a polyisocyanate curing agent.

[0006] In the formula A of the structural adhesive, the mass fraction of the catalyst is 0.01-0.1 wt %, and the mass fraction of the organic conductive material is 1-5 wt %.

[0007] The heat-curing conductive polyurethane structural adhesive and the preparation method thereof of the present invention make full use of the combination of polyester / polyether diol, catalyst and organic conductive material, so that the organic conductive agent can be evenly dispersed in the colloid, thereby significantly improving the conductive performance of the colloid. By adjusting the ratio of different components, users can optimize the conductivity according to specific application requirements. In addition, the use of polyisocyanate curing agent enables the glue to react quickly during the heating and curing process, greatly improving the curing efficiency. Specifically, within a short time (about 10 minutes) of heating to 150°C, the glue can be effectively cured to form a polyurethane structural adhesive with excellent mechanical strength and conductive properties. The cured colloid exhibits good flexibility and high elongation at break, while maintaining stable conductivity, making its application in high temperature environments more reliable. The innovation of this technology makes the conductive polyurethane structural adhesive of the present invention have significant application value in the fields of automobiles, aviation and electronic products, meeting the growing demand for high-performance adhesive materials.

[0008] Compared with the prior art, the present invention has the following beneficial effects: First, by optimizing the ratio of polyester / polyether diol and organic conductive material, the conductive properties of the colloid are greatly improved, so that the cured material has stable conductivity. Secondly, by utilizing the rapid curing characteristics of the polyisocyanate curing agent, the production cycle is shortened and the production efficiency is improved. In addition, the prepared polyurethane structural adhesive exhibits excellent mechanical strength and high elongation at break under high temperature conditions, ensuring that excellent performance is maintained under extreme conditions. This colloid is particularly suitable for the automotive, aviation and electronic product fields, and has broad application prospects and significant market value. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is the infrared spectrum of the cured polyurethane structural adhesive in Example 1 of the present invention. DETAILED DESCRIPTION

[0010] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0011] Example 1 In this embodiment, polyethylene glycol (PEG, molecular weight 600, 300g) is used as polyester / polyether diol, supplemented with a catalyst (dibutyltin diglycolate, 0.5g) and an organic conductive material (polyaniline, PANI, 4g). These components are added to a stirring kettle and stirred evenly as A glue. Under the condition of not exceeding 30 degrees Celsius, HDI trimer curing agent (35g, B glue) is added for further stirring to obtain a conductive polyurethane structural adhesive.

[0012] When in use, apply the mixed AB glue evenly to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then accurately align the parts coated with AB glue with the parts to be bonded (PET sheet). Finally, heat cure at 120 degrees Celsius for 2 hours. The test results show that the structural adhesive has a conductivity of 3.5 S / m, a bonding strength of 12MPa, a curing efficiency of 98% and good flexibility. There is no crack after bending, which meets the performance requirements. Example 2

[0013] In this example, polypropylene glycol (PPG, molecular weight 800, 250g) was selected as the polyester / polyether diol, and a catalyst (lead-based catalyst, 0.1g) and an organic conductive material (polypyrrole, PPy, 4.5g) were added to a stirring kettle and stirred evenly as glue A. Under the condition of not exceeding 30 degrees Celsius, triphenylmethane triisocyanate (30g, glue B) was added for further stirring to obtain a conductive polyurethane structural glue.

[0014] When in use, apply the mixed AB glue evenly to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then accurately align the parts coated with AB glue with the parts to be bonded (PET sheet). Finally, heat cure at 130 degrees Celsius for 2 hours. The test results show that the conductivity of the structural adhesive is 3.2 S / m, the bonding strength reaches 11 MPa, the curing efficiency is 96%, and it has good flexibility and no cracks after bending, meeting the expected performance requirements. Example 3

[0015] This example uses polytetrahydrofuran (PTMG, molecular weight 300, 280g) as polyester / polyether diol, with a catalyst (dibutyltin diglycolate, 0.3g) and an organic conductive material (polyethylenethiophene, PEDOT, 3g). These components are added to a stirring tank and stirred evenly as A glue. Under the condition of not exceeding 30 degrees Celsius, dimethyl triphenylmethane tetraisocyanate (30g, B glue) is added for further stirring to obtain a conductive polyurethane structural adhesive.

[0016] When in use, apply the mixed AB glue evenly to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then accurately align the parts coated with AB glue with the parts to be bonded (PET sheet). Finally, heat cure at 150 degrees Celsius for 2 hours. The test results show that the conductivity of the structural adhesive is 3.0 S / m, the bonding strength is 10 MPa, the curing efficiency reaches 97%, and it has good flexibility and no cracks after bending, achieving the expected performance indicators. Example 4

[0017] In this embodiment, polyethylene glycol (PEG, molecular weight 400, 200g) is used as polyester / polyether diol, and a catalyst (dibutyltin diglycolate, 0.1g) and an organic conductive material (polyaniline, PANI, 1g) are used. These components are added to a stirring kettle and stirred evenly to form glue A. Under the condition of not exceeding 30 degrees Celsius, HDI trimer curing agent (20g, glue B) is added for further stirring to obtain a conductive polyurethane structural glue.

[0018] When in use, the mixed AB glue is evenly applied to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then the parts coated with AB glue are accurately aligned with the parts to be bonded (PET sheet). Finally, thermal curing is carried out at 120 degrees Celsius for 0.5 hours. The test results show that the conductivity of the structural adhesive is only 1.2 S / m, the bonding strength is only 5 MPa, the curing efficiency is 85%, and the flexibility is poor. Cracks appear after bending, and the expected performance standards are not met. Example 5

[0019] In this example, polypropylene glycol (PPG, molecular weight 800, 150g) was selected as the polyester / polyether diol, and a catalyst (lead-based catalyst, 0.05g) and an organic conductive material (polypyrrole, PPy, 1g) were added to a stirring kettle and stirred evenly as glue A. Under the condition of not exceeding 30 degrees Celsius, triphenylmethane triisocyanate (15g, glue B) was added for further stirring to obtain a conductive polyurethane structural glue.

[0020] When in use, apply the mixed AB glue evenly to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then accurately align the parts coated with AB glue with the parts to be bonded (PET sheet). Finally, heat cure at 120 degrees Celsius for 2 hours. Test results show that the conductivity of the structural adhesive is only 0.8 S / m, the bonding strength is 3 MPa, the curing efficiency is only 75%, the flexibility is poor, and it breaks after bending, which obviously fails to meet the expected performance requirements. Example 6

[0021] In this example, polytetrahydrofuran (PTMG, molecular weight 200, 100g) is used as polyester / polyether diol, supplemented with a catalyst (dibutyltin diglycolate, 0.05g) and an organic conductive material (polyethylenethiophene, PEDOT, 1g). These components are added to a stirring kettle and stirred evenly as glue A. HDI trimer curing agent (10g, glue B) is added and further stirred at a temperature not exceeding 30 degrees Celsius to obtain a conductive polyurethane structural glue.

[0022] When in use, the mixed AB glue is evenly applied to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then the parts coated with AB glue are accurately aligned with the parts to be bonded (PET sheet). Finally, thermal curing is carried out at 150 degrees Celsius for 2 hours. The test results show that the conductivity of the structural adhesive is 0.6 S / m, the bonding strength is 2 MPa, the curing efficiency is 70%, and the flexibility is poor. It breaks after bending, fails to meet the performance standards, and shows unqualified characteristics.

[0023] Examples 1, 2, and 3 are cases with better effects. Due to different raw materials and ratios, the corresponding tape performance varies according to different application scenarios. Examples 4, 5, and 6 do not meet the limited range of the molar ratio of the polyester / polyether diol in glue A to the isocyanate group in the polyisocyanate in glue B, and the content of the organic conductive material is too low, resulting in failure to achieve the expected performance standards. The infrared spectrum of the structural adhesive after curing in Example 1 is shown in Figure 2. Figure 1 As shown, the functional groups above are shown to contain polyurethane bonds. Comparative Example 1

[0024] In this embodiment, polypropylene glycol (PPG, molecular weight 800, 300g) is used as polyester / polyether diol, supplemented with a catalyst (dibutyltin diglycolate, 0.5g) and an organic conductive material (polyaniline, PANI, 1g). These components are added to a stirring kettle and stirred evenly as glue A. Under the condition of not exceeding 30 degrees Celsius, HDI trimer curing agent (35g, glue B) is added for further stirring to obtain a conductive polyurethane structural glue.

[0025] When in use, apply the mixed AB glue evenly to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then accurately align the parts coated with AB glue with the parts to be bonded (PET sheet). Finally, heat cure at 120 degrees Celsius for 2 hours. Test results show that the conductivity of the structural adhesive is only 1.5 S / m, the bonding strength is only 8 MPa, the curing efficiency is 90%, the flexibility is poor, and cracks appear after bending. Comparative Example 2

[0026] In this embodiment, polyethylene glycol (PEG, molecular weight 600, 300g) is used as polyester / polyether diol, supplemented with a catalyst (dibutyltin diglycolate, 0.5g) and an organic conductive material (polyethylenethiophene, PEDOT, 3g). These components are added to a stirring kettle and stirred evenly to form glue A. HDI trimer curing agent (20g, glue B) is added and further stirred at a temperature not exceeding 30 degrees Celsius to obtain a conductive polyurethane structural glue.

[0027] When in use, apply the mixed AB glue evenly to the surface to be bonded (PET sheet) in a certain proportion to ensure uniform coverage. Then accurately align the parts coated with AB glue with the parts to be bonded (PET sheet). Finally, heat cure at 120 degrees Celsius for 2 hours. Test results show that the conductivity of the adhesive is 2.0 S / m, the bonding strength is 9 MPa, the curing efficiency is 85%, but the flexibility is poor and cracks appear after bending.

[0028] Comparative Example 1 Based on Example 1, polyethylene glycol (PEG) was replaced with polypropylene glycol (PPG), and the amount of conductive material was reduced, resulting in a significant decrease in conductivity to 1.5 S / m, a decrease in bonding strength to 8 MPa, a curing efficiency of 90%, and poor flexibility. This result shows that the type of polyglycol and the proportion of conductive materials have an important influence on performance. Comparative Example 2 reduces the amount of HDI trimer curing agent in Example 1 and replaces it with polyvinylthiophene (PEDOT). The test results show that the conductivity is 2.0 S / m, the bonding strength is 9 MPa, the curing efficiency is reduced to 85%, and the flexibility is poor. This further emphasizes the importance of the selection of curing agent and conductive material to the final performance. In terms of overall performance, both comparative examples show a significant decrease in performance, verifying the key influence of the selection and ratio of raw materials on performance indicators such as conductivity, bonding strength, curing efficiency and flexibility in conductive polyurethane structural adhesives. By comparing with qualified examples, the influence of material composition on performance can be more clearly recognized.

[0029] Table 1 Performance test results of conductive polyurethane structural adhesives in different embodiments and comparative examples

[0030] The above description is only part of the embodiments of the present invention and is not intended to limit the present invention. All equivalent changes and modifications made according to the content of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing a heat-curing conductive polyurethane structural adhesive, characterized in that: The following steps are involved: Polyester / polyether diol, catalyst and organic conductive material are used as glue A of the two-component glue, and polyisocyanate curing agent is used as glue B. The glue A and glue B constitute a polyurethane structural adhesive with conductive properties.

2. The method for preparing a heat-curing conductive polyurethane structural adhesive according to claim 1, characterized in that: The mixed curing process of glue A and glue B is as follows: evenly apply glue A and glue B mixed in a certain proportion on the surface to be bonded to ensure uniform coverage, accurately align the parts coated with glue A and glue B with the parts to be bonded, and finally, heat cure the bonding parts containing glue A and glue B at 80-170 degrees Celsius, and the reaction time is 0.5-3 hours.

3. The method for preparing a heat-curing conductive polyurethane structural adhesive according to claim 1, characterized in that: The polyester / polyether diol is one or more of polyethylene glycol, polypropylene glycol, polybutylene glycol, polytetrahydrofuran, polycaprolactone, and polycarbonate diol, and has a molecular weight between 200 and 1000.

4. The method for preparing a heat-curing conductive polyurethane structural adhesive according to claim 1, characterized in that: The polyisocyanate is one or more of HDI trimer curing agent, triphenylmethane triisocyanate or dimethyltriphenylmethane tetraisocyanate.

5. The method for preparing a heat-curing conductive polyurethane structural adhesive according to claim 1, characterized in that: The catalyst is a tin-based catalyst and a lead-based catalyst.

6. The method for preparing a heat-curing conductive polyurethane structural adhesive according to claim 4, characterized in that: The tin-based catalyst is one of dibutyltin diglycolate and dibutyltin diallyl oxide.

7. The method for preparing a heat-curing conductive polyurethane structural adhesive according to claim 1, characterized in that: The organic conductive material is one or more of polyaniline, polypyrrole or polyvinylthiophene.

8. The method for preparing a heat-curing conductive polyurethane structural adhesive according to claim 1, characterized in that: The molar ratio of the polyester / polyether diol in glue A to the isocyanate group in the polyisocyanate in glue B is between 0.95:1 and 1:1.

05.

9. A heat-curing conductive polyurethane structural adhesive, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It comprises glue A and glue B, wherein the glue A is composed of polyester / polyether diol, a catalyst and an organic conductive material; and the glue B is a polyisocyanate curing agent.

10. The heat-curing conductive polyurethane structural adhesive according to claim 9, characterized in that: The structural adhesive A comprises 0.01-0.1 wt % of a catalyst and 1-5 wt % of an organic conductive material.

Citation Information

Patent Citations

  • Organic silicon modified polyurethane conductive adhesive

    CN111777969A

  • Antistatic polyurethane glue as well as preparation method and application thereof

    CN115044340A

  • Elastic self-adhesive conductive sealing gasket with composite structure and preparation method of elastic self-adhesive conductive sealing gasket

    CN115926665A

  • Conductive urethane resin

    JP2005113082A

  • Electroconductive urethane composition and electroconductive roller

    JP2008056941A